Shear bond strength of composite resin cements to ceramics - Özyöney Gürol; Yanıkoğlu, Funda; Tağtekin, Dilek; Özyöney Nuran; Öksüz, Mustafa (My University, 2013)
The study aimed to evaluate the comparison of the shear bond strength of IPS Empress II and recent IPS e.max ceramics luted with eight different luting resins tested with three adhesion types: total etch, self-etch or self-adhesion. Two cylindrical shaped (7.2 mm×4.1 mm) ceramic specimens (IPS Empress II® , IPS e.max® ) were used for each test group yielding a total number of 160 specimens. The specimens in each group which were randomly divided into 8 groups (n:10) were luted with eigth different resin composite luting cements (Variolink with Heliobond adhesive system, Bifix QM with Solobond Plus adhesive system, Choice with One Step Plus adhesive system, Multilink with Primer A+B adhesive system, Bifix QM with Futurabond DC adhesive system, experimental self adhesive luting resin, G-cem self adhesive luting resin, BisCem self adhesive luting resin). In all specimens, HF (5%) and silane were applied. All specimens were stored in water for 24 h and then subjected to 10000 cycles of thermocycling (5 Cº and 55 Cº). Bond strength was measured by means of a shear test, using Zwick Z010® universal testing machine with 0.5 mm/min speed until failure. To determine the statistical significance of the differences between the mean shear bond strength values, KruskalWallis, Dunn’s multiple comparisons test and Mann-Whitney U tests were used. Shear bond strength of luting resins using totaletch system showed better mean values than the resin cements using self etch and self adhesive systems (total etch 22.40 ±9.95; self-etch 16.76±7.78; self-adhesive 8.05±3.04 for IPS Empress II) (total etch 20.44±5.48; self-etch 17.59±5.18; self-adhesive 8.41±3.27 for IPS e.max). The shear bond strength values of self adhesive system were significantly lower (P<0.05) than the other systems. No significant differences were observed between IPS Empress and IPS e.max ceramics according to shear bond strength. Adhesive failure was the most prevalent type of failure for both IPS Empress® and IPS e.max® . IPS Empress II® ceramics gave promising results, using with totaletch adhesive systems under the conditions of this in vitro study. Keywords: IPS Empress II® , IPS e.max® , shear bond strength, luting resin, total ecth, self etch, self adhesive.
Keywords: IPS Empress II® , IPS e.max® , shear bond strength, luting resin, total ecth, self etch, self adhesive.